Dinamika Kinerja Pegawai Negeri Sipil: Pengaruh Beban Kerja, Disiplin dan Motivasi di Lingkungan Kementerian Ketenagakerjaan - Fatmawati, Krisna; Lestari, Setyani Dwi (DAS Institute, 2025)
This research analyzes the influence of Workload, Work Discipline, and Work Motivation on the Performance of Civil Servants within the Manpower Planning and Development Agency, Ministry of Manpower. The method used is a survey with a specifically determined sample size, in order to obtain an accurate representation of the employee population. Data was collected through a questionnaire whose validity and reliability have been tested. Data analysis was carried out using the SPSS application through a series of tests, such as validity, reliability, correlation, multiple linear regression and classical assumption tests. This process aims to ensure that the relationship between the variables Workload, Work Discipline and Work Motivation with Employee Performance can be analyzed comprehensively and accurately. The research results show that these three variables have a significant influence on employee performance, although their influence only explains part of the variation in performance. These findings emphasize the need to improve workload management, consistent implementation of work discipline, and provide effective work motivation in order to achieve more optimal employee performance